2014
DOI: 10.1186/1472-6882-14-207
|View full text |Cite
|
Sign up to set email alerts
|

Selective apoptotic cell death effects of oral cancer cells treated with destruxin B

Abstract: BackgroundRecent studies have revealed that destruxins (Dtx) have potent cytotoxic activities on individual cancer cells, however, data on oral cancer cells especial human are absent.MethodsDestruxin B (DB) was isolated and used to evaluate the selective cytotoxicity with human oral cancer cell lines, GNM (Neck metastasis of gingival carcinoma) and TSCCa (Tongue squamous cell carcinoma) cells, and normal gingival fibroblasts (GF) were also included as controls. Cells were tested with different concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Our previous studies have demonstrated that DB treatment significantly suppressed tumorigenesis in different cancer types [ 13 , 14 , 15 , 27 , 28 ]. In this study, we examined the potential inhibitory effect of DB using 5-FU resistant colon cancer cells, induced by IGF1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have demonstrated that DB treatment significantly suppressed tumorigenesis in different cancer types [ 13 , 14 , 15 , 27 , 28 ]. In this study, we examined the potential inhibitory effect of DB using 5-FU resistant colon cancer cells, induced by IGF1.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, natural resources still remain as a valuable pool for anti-cancer drug discovery. Destruxin B (DB) is a cyclic depsipeptide produced by various species of fungi, and has been previously shown to inhibit proliferation and induce apoptosis in different cancer cells [ 12 , 13 , 14 ], making it a drug candidate for further development. Here, we showed that DB treatment not only suppressed colon tumorigenesis, but also CSC phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The promising anticancer effects were revealed by the study of destruxin B in colorectal cancer models and specifically as an inhibitor of the Wnt/beta‐catenin/Tcf signaling pathway in colorectal cancer (Table ) and hepatocellular carcinoma cells with promising results. In addition, promising anticancer activity has also been recently demonstrated for destruxin B in oral cancer cells …”
Section: Fungal Metabolites and Their Synthetic Analogues Evaluated Imentioning
confidence: 99%
“…Accordingly, destruxins are discussed as candidates for the development of novel therapeutics for the treatment of diverse maladies such as hepatitis B [ 21 – 24 ], liver fibrosis [ 25 ], osteoporosis [ 26 ] or Alzheimer’s disease [ 27 ]. In the field of cancer research, destruxins have been investigated in vitro for their therapeutic potential against oral carcinomas [ 28 ], leukemia [ 29 – 31 ], lymphomas [ 32 ], non-small cell lung cancer [ 33 ], hepatocellular carcinoma especially in combination with the tyrosine kinase inhibitor sorafenib [ 34 ], and colorectal cancer [ 20 ]. Additionally, significant anticancer activity of dtxB was reported in vivo against colorectal cancer in two studies using HT-29 xenograft mouse models without observing any dtxB-related adverse effects [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%